Zero Risk Cardiovascular Health Check: Strategi Promotif-Preventif Melalui Edukasi dan Skrining Penyakit Jantung Pada Remaja di SMK Suryalaya - Yuningsih, Aneng; Suprapti, Betty; Syarifuddin, Iman; Asparina, Arina; Bilhamdilah, Zalfa Nabilah; Gustiani, Mia Ruhmiati; Nuraeni; Ramadhan, Gilang; Ismawi, Ade Sayid (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Cardiovascular diseases remain the leading cause of mortality worldwide, with early prevention efforts ideally started during adolescence. Risk factors such as high blood pressure, obesity, and poor lifestyle habits often emerge during the teenage years and require promotive-preventive strategies within the school environment. Objective: The purpose of this service was to increase cardiovascular health awareness and conduct early screening of cardiovascular risk factors among vocational high school students. Method: This public service was conducted by lecturers and students of the Nursing and Professional Nurse Program at Universitas Bakti Tunas Husada. The activities included questionnaire screening (Z-CHECK), vital signs measurement (blood pressure, heart rate, BMI), fitness testing using the Modified Step Test, health education, and pre–post knowledge assessment. A total of 66 students from grades X and XI at SMK Suryalaya participated in the program on May 27, 2025. Result: The screening showed that 6 students had hypertension, 23 had hypotension, and 9 were obese. One student had irregular pulse, while all others showed normal cardiovascular fitness levels. Knowledge scores improved significantly from a pre-test average of 60 to a post-test average of 82. Conclusion: The program effectively identified early cardiovascular risk factors and significantly increased students’ knowledge about heart health. This model is applicable for school-based health promotion and prevention programs.